SMEs Employee, Person-Organization Fit, and Organizational Citizenship Behaviour - Faidal, Faidal (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
SMEs will get the maximum production when their employee get work satisfaction. They will work efficient when their workplace is comfortable. So the objective of this research is to analyze the influence of the workplace and Person-Organization Fit to Organizational Citizenship Behaviour (OCB) through employee satisfaction as a variable intervening at the Indonesia SMEs. This study using a random sampling of employees of Indonesia SMEs with the number 250 employees of SMEs. Instruments that are used in this research is a questionnaire to obtain the primary data needed. The research method is quantitative analysis, the data obtained is based on the answers from respondents on the questionnaire, analyzed by statistical techniques of multiple linear regression analysis, the regression model is tested with classical assumptions to meet the requirements and is suitable to be used to predict the effect of independent variables on the dependent variable. The results of the regression calculations were tested using the t-test and the coefficient of determination. The research finding have shown that variable Workplace and person-organization Fit influential to Organizational Citizenship Behaviour through employee satisfaction on the employees of Indonesia SMEs. In research, it is known that the Workplace is a variable independent that influences the most substantial of the Organizational Citizenship Behaviour of employees compared to variable independent else.